PERKEMBANGAN SENI MUZIK DALAM PERADABAN ISLAM DI NUSANTARA - Yusof, Abdullah; Bidin, Awerman (Journal of Al-Tamaddun, 2008)
This article aims to expose the status of music in a country where majority of its people follow the Islamic faith. Music in this country does not hold a great position and this indicates that musical creativity is always questioned within Islamic law such as in Indonesia. This indication is not precise without understanding the meaning and purpose behind the music. Music represents a creation of man and constitutes as a part of art, meanwhile, art is one of the cultural aspects in human life. Therefore, culture is related to art and also one of the aspects of Islamic religion?s values. Accordingly, art represents an aspect of Islamic religion. Hence, in Islam art is not part of the religion, rather it is part of Islamic cultures. The type of music that always been implemented by Moslems throughout the world is of melodic strains with the sweet voice during a call to prayer, for every newly born baby boy this called as Azan while Qamat is to be practiced when a baby girl is born.